On the Electronic Effect of V, Fe, and Ni on MgO(100) and BaO(100) Surface: An Explanation from a Periodic Density Functional - Rafael Añez; Aníbal Sierraalta (Journal of Chemistry)
A periodic density functional study of the V, Fe, and Ni sublayer doped MgO(100) and BaO(100) surfaces was carried out using a periodic approach in the context of the GGA approximation. Results suggest that doping atoms accommodate better in the MgO than in BaO because covalent radii of the doping atoms are closer to that of the Mg atom. Sizes of the doping atom, bulk forces, and electronic effects play an important role in the structural changes observed in doped surfaces studied herein. From all the doped studies, Ni doped Ba(100) surface is shown to be a promising material for trapping molecules with partially occupied states.